Pengukuran Kedalaman dan Koordinat Jalan Berlubang Menggunakan Sensor Ultrasonik dan GPS Berbasis Internet Of Things (IoT) - Phisca Aditya Rosyady; Fadil Fajeri; Muhammad Andika Agustian (Institut Teknologi Dirgantara Adisutjipto, 2022)
The development of the world of transportation in Indonesia is growing very rapidly, especially in the field of land transportation. This can be seen from the number of motorized vehicles, both cars, and motorcycles in Indonesia, which continues to increase from year to year. According to data from Badan Pusat Statistik (BPS), the number of motorized vehicles reached 126,508,776 units, the data increased 5.9 percent from the previous year 2017 wherein that year the number of motorized vehicles was 118,922,708 units. The problem that still often occurs for land transportation infrastructure is that there are still many damaged roads such as potholes, so prevention is needed by recording road damage data such as the depth of holes during manual recording, so in this study, we discuss how to measure these holes using ultrasonic sensors. integrated with GPS data to record the location of potholes. The result is that the measurement error using ultrasonic is 4.9 %. Meanwhile, for the results of testing the GPS data, the error in latitude data is 0.00061 %, the data for longitude error is 0.00004 %..